Dampak Media Sosial Terhadap Perkembangan Moral Siswa Di SMA Negeri - Nurharsyah Khaer Hanafi; Andika Wahyudi Gani; Suci Rahmadani Suhardi (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2023)
media use and (2) teachers’ efforts to address inappropriate moral development among students at SMA Negeri 1 Sendana. The research employed a qualitative descriptive approach using observation, interviews, and documentation involving 9 teachers and 20 students. Data were analyzed through reduction, display, and conclusion drawing. The findings reveal that social media exerts dual effects on students’ moral development. Positive impacts include increased independence, creativity, curiosity, and religiosity. Negative impacts include decreased interpersonal communication, discipline, politeness, reading interest, and a tendency toward risky social interaction. Teachers’ interventions align with stages of moral development: preconventional, conventional, and postconventional. At the preconventional stage, teachers apply rules and educational sanctions; at the conventional stage, they emphasize role modeling and moral habituation; and at the postconventional stage, they instill principles for wise and responsible social media use.